Mine Drainage System Planning At PT Putra Coal in The North Kalimantan Region - Sari, Avellyn Shinthya; Cahyono, Yudho Dwi Galih; Seran, Lucitania Grasella Rotyn (Journal of Applied Sciences, Management and Engineering Technology, 2024)
Coal is a deposit of plant fossils that has undergone a peat process over a long period of time. A company in Malinau Regency, North Kalimantan Province, requires replanning for the existing drainage system because its holding pond or sump, which is a former pit, will be re-mined. Therefore, this research re-plans the drainage system to overcome this problem. The methods for data processing comprised the Gumbel method, the Monobe equation, the Seyhan equation, and the calculations of open channels and holding pond dimensions, as well as pump capacity. The mine drainage system creates channels or ditches that function to prevent runoff water from entering the mining area. The channel capacity was 0.6 m3 /second, or 2,261 m3 /hour, with a large runoff of 0.146 m3 /second, or 63 m3 /hour. The channel would be made in a trapezoid shape. Meanwhile, the mine dewatering method used a pumping system to release water into the sump. Using 1 pump of MF-420EX, the total flow of water that could be pumped reached 50,537 m3 /hour with working hours of 20 hours. The sump capacity was 28,825 m3 in a trapezoid shape with dimensions of 95 m surface length, 70 m surface width, 85 m base length, 60 m base width, and 5 m depth.